(untitled) (Revista Internacional de Formação de Professores, 2022)
The present article is part of a dissertation for Sciences Education, in a research carried through with undergraduates students in chemistry, of the do Instituto Federal do Rio de Janeiro (IFRJ), campus Nilópolis. The objective was to investigate as undergraduates’ students can assume themselves of televising propagandas as didactic resource. The research was qualitative, with interpretative analysis of the information gotten in the meeting that had occurred in one of the pedagogical workshops. All the registers of the quarrels had been made in audio, and the analyzed results according to the methodology of Discursive Textual Analysis (DTA), observing the contributions of its practical development for the pedagogical one of the undergraduates’ students in question for the formation of professors. The participants of the research had carried through assays of pedagogical intervention with television advertisements, where groups of quarrels on the use of this mediatic resource had been organized as methodological option, and of the current problems in the chemistry education, beyond the difficulties of if contemplating the Practice as Curricular Component (PCC) in the teacher training. The quarrels in group had served subsidies for undergraduates students could think and rethink the pedagogical practice in the search for a more diverse chemistry teaching.